Analysis Of The Mechanical Properties Of Brick With The Addition Of Cotton - Ety Jumiati; Nita Zahara Nasution; Abdul halim Daulay (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2020)
AbstractIt has been done making bricks with the addition of cotton.Variations in the mixture of cement, sand and cotton are sample A (30%:70% :0%), sample B (30%:69,5%:0,5%), sample C (30%:69%:1%), sample D (30%:68,5%:1,5%), Water Cement Factor of 0,5 and dry time one day. Characteristic of the tests carried out include: compressive strength and fracture strength.Analysis of the mechanical properties of the bricks produced in sample A with a compressive strength value = 28.81 kg/cm2 and fracture strength value = 23.11kg/cm2, sample B with acompressive strength value = 26.85 kg/cm2 and fracture strength value = 22.32 kg/cm2, sample C with a compressive strength value = 25.10 kg/cm2 and fracture strength value = 15.09 kg/cm2, sample D with a compressive strength of 17.14 kg/ cm2 and a fracture strength value 15.51kg/cm2. The bricks produced namely in sample B.Keywords :Bricks, Cotton, and Cement